2010
DOI: 10.1038/cdd.2010.14
|View full text |Cite
|
Sign up to set email alerts
|

Cell reprogramming: expectations and challenges for chemistry in stem cell biology and regenerative medicine

Abstract: The possibility of reprogramming adult somatic cells into pluripotent stem cells (iPSCs) has generated a renewed interest into stem cell research and promises to overcome several key issues, including the ethical concerns of using human embryonic stem cells and the difficulty of obtaining large numbers of adult stem cells (Belmonte et al., Nat Rev Genet, 2009). This approach is also not free from challenges like the mechanism of the reprogramming process, which has yet to be elucidated, and the warranties for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 99 publications
(112 reference statements)
0
27
0
Order By: Relevance
“…At our present level of knowledge, failure of full and uniform reprogramming in iPSCs might result in resistance to differentiation and to an increase in the risk of teratoma formation, with poor control over self-renewal of pluripotency after transplantation. In the last few years, several new non-genetic reprogramming methods have been proposed, such as chemically induced pluripotent cells (Anastasia et al, 2010), which can be obtained with recombinant proteins or with small synthetic molecules; these might represent a simpler and safer approach. This will not only be useful for the improvement of iPSC technology, but it will also contribute to better characterize the signalling pathways that operate in iPSC induction, which will itself open new avenues for mechanistic dissection of these reprogramming processes.…”
Section: Concluding Future Remarksmentioning
confidence: 99%
“…At our present level of knowledge, failure of full and uniform reprogramming in iPSCs might result in resistance to differentiation and to an increase in the risk of teratoma formation, with poor control over self-renewal of pluripotency after transplantation. In the last few years, several new non-genetic reprogramming methods have been proposed, such as chemically induced pluripotent cells (Anastasia et al, 2010), which can be obtained with recombinant proteins or with small synthetic molecules; these might represent a simpler and safer approach. This will not only be useful for the improvement of iPSC technology, but it will also contribute to better characterize the signalling pathways that operate in iPSC induction, which will itself open new avenues for mechanistic dissection of these reprogramming processes.…”
Section: Concluding Future Remarksmentioning
confidence: 99%
“…Later, some reports showed that reversine had a role in regeneration (Anastasia et al 2006;Kim et al 2007;Saraiya et al 2010;Anastasia et al 2010;Jung and Williams 2011). Moreover, a recent report showed that reversine had anti-tumor capabilities such as for a myeloma cell line (McMillin et al 2010), and demonstrated that reversine could suppress the expression of cell cycle related proteins Aurora kinase A (Aur-A) and Aurora kinase B (Aur-B), and also could suppress enzymes involved in cell growth signaling, such as JAK2 and SRC (McMillin et al 2010;Hua et al 2012;Shan et al 2007;Jemaà et al 2012;Kuo et al 2012;Hsieh et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, unexpected inconsistencies might be related with several strategies of recruitment and maturation of stem cells and using of different types of stem cells. On the other hand, DM patient populations are not uniform that negatively associates with results of stem cells transplantation [12,13] . The purpose of the review was to summarize and analyse data for knowledge and prospects for future researches in the field of regenerative therapy in DM patients.…”
Section: Introductionmentioning
confidence: 99%